An Experimental And Finite Element Analysis Of The Static Deformation Of Wood Sawdust-Polyporpylene Composite Pallet [ TA347.F5 K45 2006 f rb]. - Khoo, Teng Sing (2006)
In this research work, a conventional stringer-class natural fiber-composite pallet model was generated using SolidWorks modeler and its load bearing capabilities and structural strength were investigated using finite element analysis software (FEA), Cosmos/works.